Trait Procrastination and Mobile Phone Addiction Among Chinese College Students: A Moderated Mediation Model of Stress and Gender - Yang, Xiaofan; Wang, Pengcheng; Hu, Ping (Frontiers in Psychology, 2020)
Recent studies indicated that trait procrastination as a personality factor could lead to mobile phone addiction, however little is known about the mediating and moderating mechanisms underlying this process. The current study investigated the mediating role of stress in the relation between trait procrastination and mobile phone addiction, and whether the mediating effect was moderated by gender. A sample included 1004 Chinese college students completed measures of trait procrastination, stress, mobile phone addiction, and demographic information. The results showed that trait procrastination was positively related to college students’ mobile phone addiction. Mediation analyses revealed that this relationship was partially mediated by stress. Moderated mediation further indicated that the path between trait procrastination and stress was stronger for male students compared with female students. These findings broadened our knowledge of the underlying mechanisms between trait procrastination and mobile phone addiction, the implications and limitations of this study were discussed.